'What is the impact of birth family contact on children in adoption and long‐term foster care?' A systematic review. (26th May 2015) - Boyle, Caroline
Abstract: Contact plans for children in adoption and long‐term foster care are decided on a case‐by‐case basis, as directed by the paramountcy principle in the Children Act (1989). The idea that birth family contact helps children resolve issues around attachment, separation and loss, and identity is prevalent in social work practice. However, evidence revealing the detrimental impact of contact has been used to support increasingly restrictive legislation. The current review aims to provide policy‐makers and social workers with a resource to guide decisions in permanency planning by evaluating this evidence and reported outcomes for children. The research question and exclusion/inclusion criteria were formulated and used to develop a search strategy. Of the 412 potential titles returned, 11 were of sufficient quality to include in the thematic synthesis. Results were mixed and significantly influenced by moderator variables such as the pre‐existing relationship between children and their birth families. Outcomes were particularly positive when there was a collaborative approach between birth families and adoptive parents or foster carers. Outcomes tended to be poorest for children who had ongoing contact with maltreating birth parents. The review findings support current policy and previous research in recommending a more reflexive approach to assessing and planning contact.